Bypass Mobile Lock Systems With Gelatin Artificial Fingerprint - EA, Maro; MM, Kovalchuk (International Journal of Computer Sciences and Engineering, 2018)
We briefly described how to bypass mobile devices lock system by using fingerprint verification. As the applying method the method of counterfeiting the fingerprint of the mobile device's owner was chosen (direct attack). The article describes the use of the method of creating a gelatin artificial fingerprints to bypass the locking system of mobile phones. The experiment confirmed the possibility of bypassing fingerprint protection without the need for expensive tools or high-quality fingerprint samples. The artificial fingerprints were tested to unlock iPhone 6 and Meizu m5s phones. To bypass lock system the iPhone 6 with a fake fingerprint we need not more than two unlock attempts. Success rate of bypass iPhone 6 biometric lock system was 70 percent. To unlock Meizu m5s we have to moistening the artificial fingerprint, after that we bypass lock system with the first unlock attempt. Success rate of bypass Meizu m5s biometric lock system was 70 percent.